The Influence of The Learning-to-Swim Method Using Fins and Swimming Boards on The Butterfly-Style Swimming Ability of SeaRIA Aquatic Athletes - Armen, Meiriani; Alben, Ary Suud Cahyo; Syahrastani, Syahrastani; Neldi, Hendri (Universitas Majalengka, 2023)
This study examines how SeaRIA Aquatic athletes' butterfly-style swimming proficiency is affected by using fins and swimming boards during the learning phase. Using a quasi-experimental methodology, the study concentrates on 55 SeaRIA Aquatic athletes. Twenty male athletes were chosen using purposive selection, and groups were created using matching strategies. A pretest, a 14-session therapy phase, and a posttest are all included in the study. The butterfly swimming ability test is used as the assessment instrument. The normality test (Liliefors) and the t-test with a significance level of α=0.05 are used in data analysis. The results show a strong relationship between the fin-and-swimming board learning approach and the improvement of butterfly swimming skills in SeaRIA Aquatic athletes. The estimated t-value of 15.37 is more than the essential t-table value of 1.81, indicating that the observed influence is significant. These findings highlight how well fins and swimming boards can be incorporated into swim training regimens for SeaRIA Aquatic athletes, especially when mastering the difficult butterfly-style technique. The consequences of this study go beyond its local setting, providing insightful information to aquatic sports organisations, coaches, and trainers looking for evidence-based methods to improve their participants' swimming skills. This study adds to the current conversation about novel and efficient ways to maximise training plans and lays the groundwork for further research on water sports education and performance improvement.